Hubungan Antara Pola Asuh Ibu Dengan Kejadian Stunting Pada Balita Usia 24-59 Bulan Di Desa Leses Kecamatan Manisrenggo Kabupaten Klaten - Agustina Funan; Chentia Misse Issabella; Yustina Ananti (Prodi Kebidanan Blora Program Diploma Tiga Poltekkes Kemenkes Semarang, 2026)
Stunting is a chronic nutritional problem characterized by a child’s height being below the standard for their age. This condition remains a major public health concern, particularly among toddlers, because it affects physical growth, cognitive development, and future productivity. Maternal parenting patterns are considered one of the important factors influencing children’s nutritional status. According to the Indonesian Nutritional Status Survey (SSGI) 2024, the prevalence of stunting in Indonesia reached 21.6%, which is still above the WHO standard of less than 20%. In Central Java Province, the prevalence slightly decreased from 20.8% in 2022 to 20.7% in 2023, but it has not yet achieved the national target of 14%. In Klaten Regency, the prevalence was recorded at 13.9%, while Leses Village had the highest prevalence in the Manisrenggo Health Center area at 23.1%. This study aimed to determine the relationship between maternal parenting patterns and the incidence of stunting among children aged 24–59 months. The study used a quantitative correlational analytical method with a cross-sectional design. A total of 55 mothers were selected through purposive sampling. Data were collected using questionnaires and observation sheets, then analyzed using the Spearman Rank test. The results showed that 65.5% of mothers had good parenting patterns, 18.2% moderate, and 16.4% poor. A significant relationship was found between maternal parenting patterns and stunting incidence (p = 0.002; r = –0.414), indicating that better parenting patterns are associated with lower stunting incidence.